ACTUAL PROBLEMS IN THE ACTIVITIES OF THE PROSECUTOR'S OFFICE AND WAYS TO SOLVE THEM IN THE CONDITIONS OF THE REPUBLIC OF UZBEKISTAN - Bakhodirov Javlon (Scholar Express Journals, 2022)
At the moment, we can talk about a very large number of functions, tasks and powers of the prosecutor's office. Developing as a separate system in the mechanism of the state, the Prosecutor's office is endowed with the rights both to conduct an investigation and to act as a party to the prosecution in court, and is endowed with issues of support for citizens and organizations in civil and economic courts. Also, the Prosecutor's office is not deprived of a law-making function, where the Prosecutor General can take an active legislative initiative. In this research work all above are studied.
Keywords: Prosecutor’s office; presecution; economic courts; execution